ANALISIS IMPLEMENTASI APLIKASI SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) DI PEMERINTAH KABUPATEN SARMI - Dastrianti Syarifuddin (Universitas Cenderawasih, 2020)
This study examines the influence of Summit Management Support and Quality of Data on the Information Systems of the Sarmi's District. The population of this research is an employee of the local government. Testing initiated on the sample of 71 respondents. We selected the data from the community using purposive sampling. Data gathering collected with the direct survey. To test our hypotheses, we employed multiple regression. The research results prove that partially proven a low - affection rate affects a positive effect against the implant information on the regional board of the region. The summon management support has a positive impact on the implant to the region information on the government's local authority. Research results also discovered that the quality of the effects is a positively influential impact against the regionals information of region management registered on the government's regional authority. Research results suggesting that a level of users, uh, peaceful management support and quality of essential influences and significant significance of implementation of the local board of region management registered in the regional, regional registry of the district geographical region of Sarmi (Y).Keywords: summit management support, data quality, Information systems.